The use of patch testing for the diagnosis of contact dermatitis: an Albanian experience - Monika Fida; Geriolda Topi; Etleva Qirko; Suela Kellici; Erjona Shehu; Orjana Dervishi; Ermira Vasili (Journal of Health Sciences, 2015)
Introduction: The daily increase of using chemical, aromatic and cosmetic products has been associated with significant increase in frequency of skin diseases such as eczemas and contact dermatitis (CD). The aim of this study was to evaluate the use of patch testing (PT) for the diagnosis of CD and provide current data on the frequency of sensitization to various contact allergens among patients with CD in the Albanian population.